PERAN PEMERINTAH DALAM MEMAKSIMALKAN MINYAK NILAM - Akbar, Arif (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
Aceh Patchouli is an export commodity product that has a high value on the global market. In fact, this great potential can increase the income of farmers and will also indirectly have an effect on the economy of the community, but this has not yet happened, many problems have arisen, ranging from rent issues, unilateral monopoly prices to the continuity of patchouli production. Therefore the role of the government as a facilitator for the development of regional potential is very much needed. Moving on from these problems, this study aims to see how the role can be done by local governments in increasing the selling value of patchouli by using Global Value Chains or GVC glasses. The election of the GVC perspective in seeing this case is certainly inseparable from the swift influence of globalization on the local government that is now happening. The government should be able to capture the current of globalization as an opportunity to improve the people's economy.